The anthropological lens as part of the training of health professionals. Experiences and reflections (Praxis Educativa, 2018)
The anthropological discipline, and particularly the density of the ethnographicmethod, consititute essential conceptual tools in the training of diverse humanistic bachelor’s degrees as well as the ones related to the health field. Specifically, in this last area the anthropological perspective is not usually included among the highlyvalued knowledge implemented by health agents who are used to trusting more, for instance, in “medical science”. In this text, a pedagogic experience of teaching anthropology applied to health field is described, considering the implementation of an elective seminar for advanced students in an Occupational Therapy bachelor’sdegree. In an auto ethnographic key, the impact of this training is analysed  taking into account that, despite being  considered “holistic” in its conception of health and human being, Occupational Therapy is highly attached to biomedical knowledge and practices.
Keywords: anthropology; occupational therapy; University; health; autoethnography